PERCEPTION OF LOCAL COMMUNITY TO HUMAN-ELEPHANT CONFLICT SURROUNDING ELEPHANT CONSERVATION HABITAT IN ACEH, INDONESIA - Abdullah Abdullah; Nazar Muhammad; Putri Hilmayanti (Aceh International Journal of Social Science, 2015)
Abstract: The aim of this research is to identify the perception of local community to human- elephant-conflict surrounding the elephant conservation habitat in Aceh Besar, Aceh Province, Indonesia. This research uses a quantitative approach and proportional sampling technique for data collection. In the process of observation, the study consideres several aspects include the description habitat disturbance of the Sumatran elephant in the conflict area, the level of damage caused by the Sumatran elephants, and how the local perception around the area of human-elephant conflict towards elephant conservation. This type of disorder that is caused by human-elephant conflict varies, from medium to moderate interference with the interpretation of a large loss. The study finds that the local perception of research sites against human-elephant conflict have good levels of perception.   Keywords: Perception of local community, Human elephants conflict, Sumatran elephant